Differential impact of renal function on the diagnostic performance of resting full-cycle ratio as non-hyperemic physiological assessment. (14th October 2021) - Ohashi, H; Takashima, H; Nawano, T; Ando, H; Nakano, Y; Sakurai, S; Suzuki, A; Suzuki, W; Amano, T
Abstract: Background: Fractional flow reserve (FFR) is a gold standard method to evaluate functional lesion severity in daily clinical practice. Recently, the resting full-cycle ratio (RFR) was Previous studies showed the better diagnostic performance of RFR comparing with FFR. It is well known that patients with chronic kidney disease (CKD) have poor prognosis. Therefore, we should carefully assess the functional lesion severity in CKD patients. However, it is unclear whether the diagnostic performance of RFR for detecting functional ischemia is similar regardless of the degree of renal function. The aim of this study is to compare the diagnostic performance of RFR based on renal function. Method: This study was a prospectively enrolled observational study. A total of 265 consecutive patients with 373 intermediate lesions were enrolled in this study. There were classified into three groups according to renal function (Group 1: eGFR ≥60 mL/min/1.73m 2 ; Group 2: 30 mL/min/1.73m 2 ≤eGFR <60 mL/min/1.73m 2 ; Group 3: eGFR <30mL/min/1.73m 2 ). The RFR was measured after adequately waiting for stable condition, while FFR was measured after intravenous administration of ATP (180mcg/kg/min). The discordance between FFR and RFR were assessed the data using known cutoffs for FFR (≤0.80) and RFR (≤0.89). Results: Of 373 lesions, the median age was 70.1±11.0 years. Functional significance was observed in 153 lesions (41.0%) of all lesions. RFR showed a significant correlation with FFR in each group (Group 1; r 2 =0.63 [p<0.001], Group 2: r 2 =0.67 [p<0.001], Group 3: r 2 =0.51 [p<0.001], respectively). The ROC curve analysis of RFR showed differential results for predicting functional significance (Group 1: AUC 0.88, cut-off value 0.91; Group 2: AUC 0.88, cut-off value 0.89; Group 3: AUC 0.81, cut-off value 0.83; respectively) in each group. The prevalence of discordant between RFR and FFR was significantly different among 3 groups (Group 1: 16.5%, Group 2: 19.4%, Group 3: 25.0%, respectively, p<0.05 for among 3 groups). Conclusion: The diagnostic performance of RFR was different based on renal function. During RFR acquisition, the degree of renal function could influence concordance with FFR, and should be taken into account when interpreting RFR. FUNDunding Acknowledgement: Type of funding sources: None.